The Impact Of Noam Chomsky’s Generative Linguistics On Modern Linguistic Science - Sukhrob Avezov Sobirovich (Genius Journals, 2024)
This paper examines the influence of Noam Chomsky’s ideas and his generative linguistics on the development of world linguistics. The main provisions of Chomsky’s theory are analysed, as well as their influence on various directions of linguistic research, such as grammar, phonology, semantics, psycholinguistics, cognitive linguistics, computational linguistics and others. The contribution of generative linguistics to the formation of the modern paradigm of knowledge about language is assessed.
Keywords: generative linguistics; Noam Chomsky; linguistics